2018
DOI: 10.14814/phy2.13719
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory and expiratory resistance cause right-to-left bubble passage through the foramen ovale

Abstract: A patent foramen ovale (PFO) is linked to increased risk of decompression illness in divers. One theory is that venous gas emboli crossing the PFO can be minimized by avoiding lifting, straining and Valsalva maneuvers. Alternatively, we hypothesized that mild increases in external inspiratory and expiratory resistance, similar to that provided by a SCUBA regulator, recruit the PFO. Nine healthy adults with a Valsalva‐proven PFO completed three randomized trials (inspiratory, expiratory, and combined external l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Intrathoracic pressure swings change rhythmically throughout the respiratory cycle and become more negative with a greater inspiratory neural drive. Thus, an increase in ventilation could, theoretically, facilitate a greater blood flow across the PFO due to greater intrathoracic pressure swings (Moses et al., 2018). In the present study, ventilation increased only ∼5 l min −1 from 21% to 10% O 2 (Table 3), which would have changed the magnitude of intrathoracic pressure swings.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathoracic pressure swings change rhythmically throughout the respiratory cycle and become more negative with a greater inspiratory neural drive. Thus, an increase in ventilation could, theoretically, facilitate a greater blood flow across the PFO due to greater intrathoracic pressure swings (Moses et al., 2018). In the present study, ventilation increased only ∼5 l min −1 from 21% to 10% O 2 (Table 3), which would have changed the magnitude of intrathoracic pressure swings.…”
Section: Discussionmentioning
confidence: 99%
“…According to PFO in cryptogenic stroke study (PICSS), a PFO is considered to be present if more than one bubble appears in the LA and if >10 appear in the LA, it is considered as a large PFO [ 25 ]. Recently, it was shown that for a given PFO, the amount of right-to-left contrast shunting is a matter of expiratory pressure during the Valsalva maneuver [ 26 ].…”
Section: Pfo In Childhoodmentioning
confidence: 99%
“…• The target tissue must be saturated with inert gas. [13][14][15] Although a large PFO is associated with an increased risk of DCS, testing of divers for PFO is only deemed necessary if divers have a history of cerebral, spinal, vestibular or cutaneous DCS, migraine with aura, cryptogenic stroke or a history of PFO or ASD in a first-degree relative. 16,17 The obvious risk mitigation strategy for such divers is to stop diving or to reduce the probability of post-dive venous gas bubbles by diving more conservatively.…”
Section: Introductionmentioning
confidence: 99%